2000
DOI: 10.1128/mcb.20.14.5010-5018.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the PTEN Tail Regulates Protein Stability and Function

Abstract: The PTEN gene is a tumor suppressor localized in the frequently altered chromosomal region 10q23. The tumor suppressor function of the PTEN protein (PTEN) has been linked to its ability to dephosphorylate the lipid second-messenger phosphatidylinositol 3,4,5-trisphosphate and phosphatidylinositol 3,4-bisphosphate and, by doing so, to antagonize the phosphoinositide 3-kinase pathway. The PTEN protein consists of an amino-terminal phosphatase domain, a lipid binding C2 domain, and a 50-amino-acid C-terminal doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
712
6
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 701 publications
(768 citation statements)
references
References 42 publications
34
712
6
5
Order By: Relevance
“…PTEN phosphorylation of various sites, including Ser380, restricted PTEN activity [24]. The dephosphorylation of PTEN also resulted in an increase of PTEN activity [24]. The treatment of B92 cells with IBMX alone or with IBMX in combination with ISO induced the dephosphorylation of PTEN, which indicated an activation of PTEN phosphatase activity (Fig.…”
Section: Camp-stimulating Agents Promote Morphological Changesmentioning
confidence: 88%
See 1 more Smart Citation
“…PTEN phosphorylation of various sites, including Ser380, restricted PTEN activity [24]. The dephosphorylation of PTEN also resulted in an increase of PTEN activity [24]. The treatment of B92 cells with IBMX alone or with IBMX in combination with ISO induced the dephosphorylation of PTEN, which indicated an activation of PTEN phosphatase activity (Fig.…”
Section: Camp-stimulating Agents Promote Morphological Changesmentioning
confidence: 88%
“…In order to further investigate the role of PTEN in cAMP-regulated cell growth, we performed western blotting analyses using the phospho-specific antibodies, phospho-PTEN (Ser380) antibody and phospho-Akt (Ser473) antibody. PTEN phosphorylation of various sites, including Ser380, restricted PTEN activity [24]. The dephosphorylation of PTEN also resulted in an increase of PTEN activity [24].…”
Section: Camp-stimulating Agents Promote Morphological Changesmentioning
confidence: 99%
“…We have provided evidence that a consensus electropositive interface in SUMO1 -PTEN facilitates cooperative binding of PTEN with the electronegative phospholipid membrane or its substrates by electrostatic interaction. Phosphorylation leads to a closed conformation that prevents PTEN association with the plasma membrane 9,10 ; however, if taken into account the electrostatic status, phosphorylation actually supplies negative charges. Th erefore, SUMOylation appears to be a positive regulator in controlling PTEN membrane association, whereas phosphorylation is a negative regulator that may neutralize SUMOylation through intramolecular electrostatic interactions.…”
Section: E N T I -V E C T O R L E N T I -V E C T O R Kdamentioning
confidence: 99%
“…Because PTEN has a critical role in antagonizing PI-3 kinase signaling pathways, it might be expected that PTEN would be the target of complex control mechanisms. Only limited studies have addressed this issue, but evidence is now emerging for functional regulation of PTEN at the level of protein stability and localization, as well as transcription of the PTEN gene (Adey et al, 2000;Vazquez et al, 2000Vazquez et al, , 2001Kurose et al, 2001;Bastola et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because PTEN has a critical role in antagonizing PI-3 kinase signaling pathways, it might be expected that PTEN would be the target of complex control mechanisms. Only limited studies have addressed this issue, but evidence is now emerging for functional regulation of PTEN at the level of protein stability and localization, as well as transcription of the PTEN gene (Adey et al, 2000;Vazquez et al, 2000Vazquez et al, , 2001Kurose et al, 2001;Bastola et al, 2002).It has been demonstrated that the activity of PI-3 kinase, the level of 3-phosphorylated PIs, and the activity of Akt are increased in cells exposed to H 2 O 2 (Konishi et al, 1997;Shaw et al, 1998;Sonoda et al, 1999;Tanaka et al, 1999;Qin et al, 2000). This H 2 O 2 -mediated activation of PI-3 kinase/Akt pathway is considered to be the result of reversible oxidation and inactivation of protein tyrosine phosphatase (PTP) family protein such as PTEN that have a critical cysteine residue in the active site (Denu and Tanner, 1998;Lee et al, 1998;Meng et al, 2002).…”
mentioning
confidence: 99%